2005
DOI: 10.1007/bf02985126
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of recurrence and hypothyroidism after radioiodine treatment in patients with hyperthyroidism in Trakya, a mild iodine deficiency area, during the period 1991–2003

Abstract: The treatment success in all groups and subgroups did not differ significantly between FD and CD. Our lower cure rate than in previous studies may be related to iodine deficiency. Higher doses of radioiodine may be required to increase final treatment success in endemic goiter areas. If this true, dosimetry and calculated dose regimen would be required in all groups of patients instead of an FD concept. However, our findings should be verified in larger series of patients, with longer follow-up period, and uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…A third study with a large difference in administered activities showed better treatment outcome in the group receiving the highest mean activity (13). The fact that in three studies the applied activities were rather similar (16,19,21), points out that the difference between the two methods does not only lead to similar treatment effects, but that it also does not translate invariably into different applied activities.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A third study with a large difference in administered activities showed better treatment outcome in the group receiving the highest mean activity (13). The fact that in three studies the applied activities were rather similar (16,19,21), points out that the difference between the two methods does not only lead to similar treatment effects, but that it also does not translate invariably into different applied activities.…”
Section: Discussionmentioning
confidence: 88%
“…Thyroid volume was determined by palpation in three studies, by ultrasound in two studies, by nuclear imaging methods in two studies; one study used a combination of the latter two methods. The used tracer activity for the 4-and 24-h uptake scan was reported in only four studies (10,13,18,21).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In three studies only multinodular toxic goiters were included (12-14). Three studies comparing fixed dose (FD) versus calculated dose (CD), included both Graves’ disease and TNG (4, 15, 16). In recent studies we extracted data for patients with toxic multinodular goiter and only analyzed that part of the trial.…”
Section: Resultsmentioning
confidence: 99%
“…U većini istraživanja na ovu temu, nije pokazana znaĉajnija razlika u ishodu zavisno od korišćenja fiksnih ili kalkulisanih doza u terapiji hipertireoidizma. Ustun i saradnici primenjivali su kalkulisane i fiksne doze od 10mCi, kod tri grupe ispitanika i nisu našli znaĉajnu razliku u odnosu na krajnji ishod [22]. U istraživanju Metso i saradnika, nakon primene fiksne doze od 7mCi pacijentima sa GB, u prvoj postterapijskoj godini bilo je 24% hipotireoidnih pacijenata, a nakon 25 godina 82% [18].…”
Section: Wwwtmgorgrsunclassified